2016
DOI: 10.2334/josnusd.15-0731
|View full text |Cite
|
Sign up to set email alerts
|

Levels of vaspin and omentin-1 in gingival crevicular fluid as potential markers of inflammation in patients with chronic periodontitis and type 2 diabetes mellitus

Abstract: Abstract:The aims of the present study were to determine the levels of vaspin and omentin-1 in gingival crevicular fluid (GCF) in patients with chronic periodontitis (CP) with and without type 2 diabetes mellitus (T2DM), and to evaluate GCF vaspin and omentin-1 levels after non-surgical periodontal therapy. The study included 60 subjects: 15 systemically and periodontally healthy individuals, 15 periodontally healthy patients with T2DM, 15 systemically healthy patients with CP, and 15 patients with both CP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
1
21
0
2
Order By: Relevance
“…Collectively, the above investigations have suggested that VASP has a potential role as an anti-inflammatory, anti-apoptotic, and antioxidant biomarker of chronic periodontitis and can be altered after non-surgical treatment in the oral cavity [17,56].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Collectively, the above investigations have suggested that VASP has a potential role as an anti-inflammatory, anti-apoptotic, and antioxidant biomarker of chronic periodontitis and can be altered after non-surgical treatment in the oral cavity [17,56].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have suggested that VASP has a potential role as an inflammatory biomarker of chronic periodontitis and can be altered after non-surgical treatment in the oral cavity [17]. Regarding oral cavity and vaspin, in three studies in which gingival crevicular fluid (GCF) concentrations were determined in patients with moderate severity of periodontitis, higher levels of this protein were found relative to the reference groups [15,17,59]. In the analyzes carried out by Pradeep et al in 2015, similar relationships were also found in the concentrations of this protein in the tear fluid [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean age of the participants ranged between 11 and 67 years. Twenty-one studies recruited both gender, 17,19,[22][23][24]27,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] four were conducted only in men, 18,21,25,47 and three used female subjects. 20,26,48 Included studies were conducted in participants with T1DM, 17,32,40 T2DM 22,23,26,27,38,39,41,[43][44][45][46][47] , and patients with IGT.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%